EAHP survey 2010 on hospital pharmacy in Europe: parts 4 and 5. Clinical services and patient safety. Issue 2 (20th February 2013) - Frontini, Roberto; Miharija-Gala, Tajda; Sykora, Juraj
Abstract : Decentralised clinical services, with a pharmacist working in the ward at least 50% of the time or with pharmacists visiting the ward daily, are not very common in Europe. For-profit hospitals offer the service remarkably less than other hospitals, and 39.8% of hospital pharmacies offer clinical services occasionally. There is a variety of patient oriented clinical activities delivered by European hospital pharmacies, including the provision of drug information, pharmacokinetic consultations, therapeutic drug monitoring, management prevention of adverse drug reactions and medication errors. Hospital pharmacy involvement in managing the interface between primary and hospital care is less common. In general, clinical activities are not well documented. For inpatients, on average, only 14.7% and 21.9% of the hospital pharmacies that took part in the survey said they write down their interventions in the medical records and in pharmacy records, respectively. IT systems are broadly used in the provision of drug information but also in profiling patient medication and for dosage calculations. Patient safety is a major interest of hospital pharmacists and, on average, 55.0% of hospital pharmacies recorded that they have implemented a system to ensure patient safety.